MAKNA PADA LIRIK LAGU DALAM ALBUM “GANG” KARYA JOHNNY HALLYDAY - Sri Herawati; Yuliarti Mutiarsih; Farida Amalia (Universitas Muhammadiyah Surabaya, 2025)
Language is used to convey emotions both directly and indirectly in various forms. Literary works are one form of language, while songs combine literary and artistic elements by merging lyrics with melody. Today, songs have become one of the most popular forms of art, though many people do not fully understand the meaning behind them. The song lyrics in Johnny Hallyday's album “Gang” are used as the object of research to analyze their meaning, focusing on Djajasudarma's theory of types of meaning. This research aims to analyze the types of meaning present in the song lyrics from the album “Gang” by Johnny Hallyday. A descriptive qualitative method is used in this study, with reading, note-taking, and literature study as data collection techniques. The results reveal 223 data points with 11 types of meaning. The 11 types of meaning found in the song lyrics of the album “Gang” include narrow meaning, broad meaning, cognitive meaning, connotative meaning, emotive meaning, referential meaning, construction meaning, lexical meaning, grammatical meaning, propositional meaning, and idiomatic meaning. Among these, lexical meaning is the most frequently appearing type. The findings of this study can be applied in semantics courses to help students understand how the theory of types of meaning is used in analyzing the meaning of a text, particularly in song lyrics, and also help learners expand their French vocabulary and gain exposure to French songs.